Effects of EPO on blood parameters and running performance in Kenyan athletes - Haile, D. W.; Durussel, J.; Mekonen, W.; Ongaro, N.; Anjila, E.; Mooses, M.; Daskalaki, E.; Mooses, K.; McClure, J. D.; Sutehall, S.; Pitsiladis, Y. P. (Medicine & Science in Sports & Exercise, 2019)
INTRODUCTION: Recombinant human erythropoietin (rHuEpo) administration enhances oxygen carrying capacity and performance at sea level. It remains unknown whether similar effects would be observed in chronic altitude-adapted endurance runners. The aim of this study was to assess the effects of rHuEpo on hematological and performance parameters in chronic altitude-adapted endurance runners as compared to sea level athletes. METHODS: Twenty well-trained Kenyan endurance runners (KEN) living and training at approximately 2150 m received rHuEpo injections of 50 IU·kg body mass every 2 d for 4 wk and responses compared with another cohort (SCO) that underwent an identical protocol at sea level. Blood samples were obtained at baseline, during rHuEpo administration and 4 wk after the final injection. A maximal oxygen uptake (V O2max) test and 3000-m time trial was performed before, immediately after and 4 wk after the final rHuEpo injection. RESULTS: Hematocrit (HCT) and hemoglobin concentration (HGB) were higher in KEN compared to SCO before rHuEpo but similar at the end of administration. Before rHuEpo administration, KEN had higher V O2max and faster time trial performance compared to SCO. After rHuEpo administration, there was a similar increase in V O2max and time trial performance in both cohorts; most effects of rHuEpo were maintained 4 wk after the final rHuEpo injection in both cohorts. CONCLUSIONS: Four weeks of rHuEpo increased the HGB and HCT of Kenyan endurance runners to a lesser extent than in SCO (~17% vs ~10%, respectively) and these alterations were associated with similar improvements in running performance immediately after the rHuEpo administration (~5%) and 4 wk after rHuEpo (~3%).